Investigation of the Effect of Occupational Noise Exposure on Blood Pressure and Heart Rate of Steel Industry Workers. (28th May 2013) - Zamanian, Zahra; Rostami, Reza; Hasanzadeh, Jafar; Hashemi, Hassan
Abstract : Background and Objectives . This study aimed to investigate the effect of noise exposure on blood pressure and heart rate of steel industry workers. Materials and Methods . In the present cross-sectional study, 50 workers were selected from a steel company in Fars province, Iran, and exposed to 85, 95, and 105 dB noise levels for 5 minutes. The participants' blood pressure and heart rate were measured using Beurer BC16 pulse meter both before and after the exposure. Results . The study results showed no significant difference in blood pressure and heart rate before and after the exposure. However, the workers' systolic blood pressure had increased compared to before the exposure; of course, the difference was not statistically significant (P > 0.05 ). Besides, although the subjects' heart rate had reduced in comparison to before the exposure, the difference was not statistically significant (P > 0.05 ). Conclusion . No significant change was observed in blood pressure and heart rate after acute exposure to 85, 95, and 105 dB noise levels.